Gut Microbiome as a Mediator of Stress Resilience: A Reactive Scope Model Framework. (11th May 2022) - Houtz, Jennifer L; Taff, Conor C; Vitousek, Maren N
Abstract: Stress resilience is defined as the ability to rebound to a homeostatic state after exposure to a perturbation. Organisms modulate various physiological mediators to respond to unpredictable changes in their environment. The gut microbiome is a key example of a physiological mediator that coordinates a myriad of host functions including counteracting stressors. Here, we highlight the gut microbiome as a mediator of host stress resilience in the framework of the reactive scope model. The reactive scope model integrates physiological mediators with unpredictable environmental changes to predict how animals respond to stressors. We provide examples of how the gut microbiome responds to stressors within the four ranges of the reactive scope model (i.e., predictive homeostasis, reactive homeostasis, homeostatic overload, and homeostatic failure). We identify measurable metrics of the gut microbiome that could be used to infer the degree to which the host is experiencing chronic stress, including microbial diversity, flexibility, and gene richness. The goal of this perspective piece is to highlight the underutilized potential of measuring the gut microbiome as a mediator of stress resilience in wild animal hosts.